Retail data warehousing notable development process determinants - Syed Nasirin Syed Zainol Abidin; Esmadi Abu Abu Sema; Hadzariah Ismail; Jackel Vui Lung Chew, Jackel; Nooralisa Mohd Tuah; Abdullah Mohd. Tahir; Suddin Lada (Springer, Cham, 2021)
For close to 25 years, the retailing industry has devoted a great deal of effort investigating the subject of how adequately to develop Retailing Data Warehousing Systems (RDWS) in their organisations. The advantages are attained when satisfactory capabilities are made within their organisations. Reviews of RDWS research have disclosed that there are enormous amounts of determinants available in the literature; however, the retailers accountable for those drives cannot suppose that the primary development forces of the system in developed nations are opulent in their regions. In response to these lapses, this study aims to assess the favourable and unfavourable effects impacting the development leadership in developing regions. Five stages of RDWS development timeframe were utilised to answer the proposed research questions, “How do these retailers go about developing the warehousing system in their company?” The sampling method employed in choosing the subjects was based on purposive sampling procedure, and the theoretical framework explained here meets the principles of functional ability submitted by previous researchers.